TANTANGAN DISFUNGSI MINAT BELAJAR BAHASA INDONESIA SISWA SMK: STUDI DESKRIPTIF DI MAMBA’UL HUDA SUMBERURIP - Syafi Junadi; Muhammad hasbullah Ridwan (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
This study aims to describe and analyze in depth the level of learning interest of class XI students of SMK Mamba'ul Huda Sumberurip towards the Indonesian Language subject. Interest is an essential psychological factor that significantly influences academic achievement in a subject. This study was conducted at SMK Mamba'ul Huda, involving 30 class XI students from 2 classes. The method used is a descriptive survey with a quantitative approach analyzed using the interpretation of percentage values, reinforced by a qualitative approach through interviews. Primary data collection was carried out by distributing questionnaires to 30 students with 30 statement items, as well as interviews with key informants (principals, teachers, and students). The results of the data analysis indicate that in general, students' learning interest is still at a level that requires serious attention, characterized by a lack of feelings of joy, motivation, interest, and active encouragement towards the Indonesian Language subject. Specific findings show that almost 46.2% of students stated that they neither agree nor disagree with the statement that they feel happy and enthusiastic in learning. The conclusion of this study confirms that interest in learning Indonesian at SMK Mamba'ul Huda Sumberurip must be increased because of the role of Indonesian as a foundation and introduction to communication in the world of education and vocational studies.